Fostering Critical Thinking and Patriotism via a Local Wisdom-Based Pancasila Education Module for Fifth Grade Students - Agung Santika; Wuri Wuryandani (South Sulawesi Education Development (SSED), 2025)
This research aims to develop: (1) a feasible local wisdom-based Pancasila education learning module to improve the critical thinking skills and patriotics character of fifth-grade students, (2) a practical local wisdom-based Pancasila education learning module for the same purpose, and (3) an effective local wisdom-based Pancasila education learning module to enhance students’ critical thinking and patriotics character. This research and development study was conducted at SDN 2 Tambakan, SDN 3 Joton, SDN 1 Kraguman, SDN Prawatan, and SDN 1 Granting in Jogonalan District, Klaten Regency, Central Java Provience. The development procedure was adapting from Borg and Gall (2003) model, which consist of ten steps: (1) preliminary study, (2) planning, (3) development of initial product, (4) initial field testing, (5) product revision, (6) main field testing, (7) product revision, (8) operational field testing, (9) final product, and (10) dissemination. The research subjects were fifth-grade students and teachers. Data were collected through interviews, observations, product validation, and feasibility questionnaire validation. Data were analyzed using both qualitative and quantitative methods. The effectiveness of module was examined through n-gain scores and the Mann Whitney U test at a 5% significance level. The findings show that (1) the module meets the criteria of feasibility based on expert validation in contect and media, (2) the module is practical according to teacher and student assessment, and (3) the module is effective in enhacing students’ critical thinking and patriotic character. The experimental class outperformed the control class in both ciritical thinking and patriotic character based on the N-gain scores. The t-test and Mann Whitney U test results yielded a signifivance value of <1%, indicating a significant effect of the module on improving students’ ciritical thinking and patriotic character.